FFF242 : Produksi kamera berbilang / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
The course exposes students to the basic technique and practice of multiple camera production for the purpose of studio recording and also of telecasting specific events or programs, either “live” or otherwise. This will be approached by means of producing television program based on composite methods to record segments as well as outside location recordings inserted as playback visuals. Students will also be trained to conduct a proper TV magazine show using multiple camera production facilities. Theories based on text book notes will be given to enhance formal education and solid exposures on conducting a proper magazine/talk show/musical show using MCP facilities in order to guide responsibilities on forming a complete version of good and quality TV program.